2008
DOI: 10.1093/wber/lhn015
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Rainfall Insurance Participation in Rural India

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
232
9
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(258 citation statements)
references
References 17 publications
16
232
9
1
Order By: Relevance
“…Despite the potential to reduce risks, farmers' demand for insurance has however been considerably lower than expected (Akter et al 2009;Giné et al 2008). Previous studies identified a range of issues influencing farmers' low insurance uptake, including financial constraints, unfamiliarity with insurance, low financial literacy, and lack of trust in insurance providers, among others (Akter 2012;Binswanger-Mkhize 2012;Clarke and Grenham 2013;Akter et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the potential to reduce risks, farmers' demand for insurance has however been considerably lower than expected (Akter et al 2009;Giné et al 2008). Previous studies identified a range of issues influencing farmers' low insurance uptake, including financial constraints, unfamiliarity with insurance, low financial literacy, and lack of trust in insurance providers, among others (Akter 2012;Binswanger-Mkhize 2012;Clarke and Grenham 2013;Akter et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…WII is also conceptually complex, disincentivizing smallholders' willingness to invest (Giné et al 2008;Akter et al 2016). This ironically results in Brisk aversion,^in which the targeted smallholder clients, especially those in risk-prone regions whom could benefit from climate change adaptation, do not understand the WII products, causing their preference to remain uninsured (Giné et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of different instruments exists, including weather-indexed insurance (i.e., policy holders are paid in response to 'trigger events' such as abnormal rainfall, for example). Weather insurance has been widely trialled and evaluated in parts of India (Giné et al, 2008). National weatherindexed crop insurance was first used in Malawi in 2008, and is still in operation, any payout being used to finance food imports or social safety net programmes in affected areas (FAO, 2012).…”
Section: Risk Managementmentioning
confidence: 99%
“…13 This subsidy remained constant from IBLI's January 2010 début through the period examined in this research, but has since decreased. 14 Uptake among studied households (e.g., surveyed, provided with additional education, included in price incentive experiments) at actuarially fair premiums is commonly less than 20% per season and often much below that (e.g., Giné, Townsend & Vickery 2008;Karlan, et al 2014;Mobarak & Rosenzweig 2012). At highly subsidized rates, uptake generally increases but is much below 100% even when the expected indemnity payments are much greater than the premium rate.…”
Section: Datamentioning
confidence: 99%